(untitled) (Research, Society and Development, 2023)
Bacteria caused by bacteria have had several negative impacts on health and the economy. Due to its potential for transmissibility, it has aroused great interest from scientists, since most of these microorganisms are resistant to antibiotics and do not have treatments and effective prophylaxis. Therefore, science has been adding information technology to analyze important data in order to obtain information, and thus be able to carry out the vaccine design against these pathogens. The objective of this study was to search in the literature and in inventions, files that were related to peptide vaccines developed from the use of bioinformatics. Peptide vaccine, bioinformatics and vaccine design were the keywords used to search for articles and patents in the following databases: PubMed, INPI and WIPO. The survey of common data found a sample of 259 scientific articles and 31 patents existing in the last 11 years in the WIPO, beyond 31 patents on the INPI. The definition of scientific-technological prospections is extremely important to provide a greater acquisition of knowledge on the subject addressed and allow the scientist to better direct the study.